Bipedal Hopping Reveals Evidence of Advanced Neuromuscular Aging Among People With Mild Multiple Sclerosis. Issue 5 (3rd September 2017) - Kirkland, Megan C.; Downer, Matthew B.; Holloway, Brett J.; Wallack, Elizabeth M.; Lockyer, Evan J.; Buckle, Natasha C. M.; Abbott, Courtney L.; Ploughman, Michelle
ABSTRACT: Measures of walking such as the timed 25-ft walk test (T25FWT) may not be able to detect subtle impairment in lower limb function among people with multiple sclerosis (MS). We examined bipedal hopping to determine to what extent people with mild (Expanded Disease Severity Scale ≤ 3.5) MS ( n = 13) would differ compared to age-, gender-, and education-matched controls ( n = 9) and elderly participants ( n = 13; ≥ 70 years old). We estimated lower limb power (e.g., hop length, velocity), consistency (e.g., variability of hop length, time), and symmetry (ratio of left to right foot). Participants completed the T25FWT and, after a rest, they then hopped using both feet 4 times along the walkway. We found that although all groups scored below the 6 -s cutoff for T25FWT, the elderly group had significantly shorter hop lengths, more variability, and more asymmetry than the controls. The results of the MS group were not significantly different from the elderly or controls in most measures and most of their values fell between the control and elderly groups. Hop length, but not measures of walking predicted Expanded Disease Severity Scale score ( R 2 = .38, p = .02). Bipedal hopping is a potentially useful measure of lower limb neuromuscular performance.